What Do We Know about the Deportation of Jews from the Warsaw Ghetto to Bobruysk and Smolensk in the Spring and Summer of 1942?. Issue 1 (2nd January 2017) - Prais, Lea
Abstract : With their occupation of territories of the USSR the Germans needed to establish a central supply base for the Waffen -SS in central and southern Russia for the group of armies that were operating there. For this purpose at the beginning of 1942 they set up, a central supply base in the forest (a Waldlager ) close to the village of Kissyelevichi, eight kilometers southeast of the city of Bobruysk in an area that was under military administration. In mid-September 1943, the Jewish camp was liquidated (although the military camp continued to function, mainly as a base for actions against the local partisan fighters). At that time about 90 Jewish prisoners remained alive. They were transferred first to Minsk and, then, about a week later to the Lublin District, where they were dispersed among several concentration camps. In addition to the deportation to Bobruysk in July 1942 and its rapidly fatal results, 500 Jews from the Warsaw ghetto were deported to the headquarters of the Luftwaffe in Smolensk. In this article, I discuss the singular features of the Jewish camp at the supply base at Bobruysk, the reasons for its establishment, and the fate of the Jews incarcerated therein, and explore why, three decades after the war, it still failed to appear on the map of the camps. An additional issue I address is the fate of the Jews from the Warsaw Ghetto who were deported to Minsk and to Smolensk at the same time – how many were deported, when, why and what is known about them.